Sexual Harassment Crime In Digital Space: Legal Challenges And Solutions - Roz, Ika Dwimaya; Saimima, Judy Marria; Salmon, Harly Clifford Jonas; Wadjo, H.Z.; Fitrian, Achmad (Journal of Strafvordering Indonesian, 2025)
In the context of rapid technological development, digital space presents significant challenges in law enforcement, especially in relation to the crime of sexual violence. Law No. 12 of 2022 on Criminal Acts of Sexual Violence provides a firm legal framework to address the problem, but is still faced with various obstacles, such as the complexity of the vast digital space, difficult identification of perpetrators, and lack of public legal awareness. Collaboration between the government, legal institutions, the technology sector, and the community is key to strengthening the prevention and handling of sexual violence cases in the digital space. Advanced forensic technology and training of skilled human resources are needed to support effective law enforcement. In addition, the integration of legal education and digital literacy programs can strengthen public understanding of the legal rights of victims and collective responsibility in maintaining digital security. This collective effort is expected to create a safe and inclusive ecosystem, and ensure better access to justice for all victims of sexual violence in the digital space.